Pembelajaran Jarak Jauh dan Kemandirian Belajar Siswa: Tantangan dan Pemecahannya selama Masa Pandemi Covid-19 di Madrasah Aliyah Kholafiyah Hasaniyah Gading Probolinggo - Rohana, Siti (Universitas Nurul Jadid, 2021)
The research is aim to describe the distance learning implementation of MA Kholafiyah Hasaniyah, its constraint factors, and its impact of the learning to the students self motivated learning. The research method is descriptive qualitative of embedded case study research in order to gather relevan data. Data collection technique is interview, observation, and documentation. The informant is the management, the teachers, and the students of MA Kholafiyah Hasaniyah. The research finding is; (1) There are some paces of distrance learning implementation of MA Kholafiyah Hasaniyah that are training program (preparation), offline learning, online learning, and home visit, and evaluation in the form of formative test, self assignment, amount of tutorial participation, and final/middle examination (PAS/PTS). (2) The constraint factors of MA Kholafiyah Hasaniyah distrance learning implementation are: low students ICT literacy, limited access to the internet, students low in self motivation and achievement, and limited of learning facilities. (3) Distance learning process of MA Kholafiyah Hasaniyah have no sufficient impact to the students self motivated learning, which d by; (a) limited capability of self regulation in learning such as time management, learning strategy, and important critical learning activities as reading, summarizing, note taking is not well programming, (b) low learning responsibility of the students in self evaluation, reflection, problem solving, and regulating learning process, and (c) limited learning resources utilization of the students.